O11.1 Herpes Simplex Virus (HSV) Infection in the VOICE (MTN 003) Study: Pre-Exposure Prophylaxis (PrEP) For HIV with Daily Use of Oral Tenofovir, Oral Tenofovir-Emtricitabine, or Vaginal Tenofovir Gel. (13th July 2013) - Marrazzo, J; Rabe, L; Kelly, C; Livant, T; Chirenje, M; Richardson, B; Deal, C; Piper, J; Hillier, S
Abstract : Background: In subSaharan Africa, HSV-2 infection is common, and increases risk of HIV transmission and acquisition. Tenofovir gel applied before and after vaginal intercourse provided partial protection from HSV-2 acquisition in the CAPRISA 004 study. We enrolled women in a 5-arm, randomised, double-blind, placebo-controlled trial assessing the safety and efficacy of daily use of oral tenofovir, oral tenofovir-emtricitabine, and 1% vaginal tenofovir gel as HIV PrEP, and assessed characteristics of women with baseline HSV and risk of HSV seroincidence during the study. Methods: From September 2009-June 2011, 12, 379 women were screened at 15 sites in South Africa, Uganda, and Zimbabwe. Eligibility criteria included normal renal, hematologic and hepatic function, report of vaginal intercourse in prior 3 months, negative pregnancy test, and willingness to use effective contraception throughout. Testing for HSV-2 type-specific antibody (Focus HerpeSelect EIA) was performed on plasma from enrollment and study exit. Results: Of 5, 029 participants, baseline HSV serology was available for 4996 (99.3%). Most were from Durban (62%), followed by Johannesburg (14%), Zimbabwe (13%), Uganda (6%), and Klerksdorp (5.2%). Mean age was 25.3 years; 79% were unmarried. Over follow-up of 5, 511 person years, end-of-study retention was 91%. Using a cutoff index value of > 3.5, 46% of participants were HSV-2 and 95% HSV-1 seropositive at enrollment. Country- and age-specific HSV-2 seroprevalence ranged from 32% (Zimbabwe) to 63% (Uganda). Seroincidence of HSV-2 by arm will be presented. Conclusions: In this population of women at risk for HIV-1, seroprevalence of HSV-2 was high, with potentially important differences by age and site of enrollment.